The Implementation of Islamic Religious Education Learning Evaluation at SMPN 1 Bukit Sundi: A Study of Assessment Planning, Implementation, and Follow-Up - Sherli Dwi Andri Saputri; Hafidz Ardi; Remiswal Remiswal; Khadijah Khadijah (The Future of Education Journal, 2026)
This study aims to examine the implementation of Islamic Religious Education (PAI) learning evaluation at SMPN 1 Bukit Sundi, Solok Regency, West Sumatra, covering aspects of lesson planning, evaluation implementation, and follow-up actions on assessment results. The study employs a descriptive qualitative approach through in-depth interviews with an experienced PAI teacher. The findings reveal that: (1) the PAI teacher has developed teaching modules based on the Merdeka Curriculum by analyzing Learning Outcomes (CP) and Learning Trajectory (ATP); (2) evaluation encompasses three domains, namely knowledge, skills, and attitudes, with average student learning outcomes ranging from 75–80 and a mastery rate of 80–85%; (3) follow-up actions through remedial and enrichment programs have been systematically implemented; (4) several challenges persist in PAI learning, including low Quranic reading ability and the influence of technology on student motivation. This study concludes that the implementation of PAI evaluation at SMPN 1 Bukit Sundi is generally running well but still requires improvements in facility provision, methodological innovation, and synergy among school, teachers, and parents.